IMPACT of COVID-19 on hip fracture services: A global survey by the International Multicentre Project Auditing COVID-19 in Trauma & Orthopaedics. Issue 4 (August 2022) - Hall, Andrew J.; Clement, Nicholas D.; MacLullich, Alasdair M.J.; Ojeda-Thies, Cristina; Hoefer, Christine; Brent, Louise; White, Timothy O.; Duckworth, Andrew D.
Abstract: Introduction: The Coronavirus Disease 2019 (COVID-19) pandemic resulted in major disruption to hip fracture services. This frail patient group requires specialist care, and disruption to services is likely to result in increases in morbidity, mortality and long-term healthcare costs. Aims: To assess disruption to hip fracture services during the COVID-19 pandemic. Methods: A questionnaire was designed for completion by a senior clinician or service manager in each participating unit between April–September 2020. The survey was incorporated into existing national-level audits in Germany (n = 71), Scotland (n = 16), and Ireland (n = 16). Responses from a further 82 units in 11 nations were obtained via an online survey. Results: There were 185 units from 14 countries that returned the survey. 102/160 (63.7%) units reported a worsening of overall service quality, which was attributed predominantly to staff redistribution, reallocation of inpatient areas, and reduced access to surgical facilities. There was a high rate of redeployment of staff to other services: two thirds lost specialist orthopaedic nurses, a third lost orthogeriatrics services, and a quarter lost physiotherapists. Reallocation of inpatient areas resulted in patients being managed by non-specialised teams in generic wards, which increased transit of patients and staff between clinical areas. There was reduced operating department access, with 74/160 (46.2%) centres reporting a >50% reduction. Reduced theatre efficiency was reported by 135/160 (84.4%) and was attributed to staff and resource redistribution, longer anaesthetic and transfer times, and delays for preoperative COVID-19 testing and using personal protective equipment (PPE). Conclusion: Hip fracture services were disrupted during the COVID-19 pandemic and this may have a sustained impact on health and social care. Protection of hip fracture services is essential to ensure satisfactory outcomes for this vulnerable patient group.